MECHANISMS FOR ENHANCING THE COMPETITIVENESS OF SMALL AND MEDIUM-SIZED ENTERPRISES IN THE PROCESS OF DIGITAL TRANSFORMATION (International journal of artificial intelligence, 2026)
In the context of the global digital economy, digital transformation has become a key determinant of competitiveness for small and medium-sized enterprises (SMEs). This article explores the mechanisms through which digital transformation enhances SME competitiveness, focusing on technological, institutional, managerial, and human capital dimensions. Based on the IMRAD structure, the study systematizes theoretical approaches, analyzes international and emerging economy experiences, and proposes an integrated mechanism for strengthening SME competitiveness under digital transformation. The research contributes novel conceptual insights suitable for PhD-level research and publication in peer-reviewed academic journals.